1977
DOI: 10.1017/s0022172400056291
|View full text |Cite
|
Sign up to set email alerts
|

Acute otitis externa in divers working in the North Sea: a microbiological survey of seven saturation dives

Abstract: SUJMMARYSaturation diving is an important and widely used technique in the Offshore Oil Industry. During 1974-5 two saturation dives in the North Sea were terminated because of outbreaks of incapacitating otitis externa, and others were disrupted. P8eudomona8 aeruginosa was consistently isolated from the ears of affected divers.Because complex work schedules were threatened seven subsequent dives were subjected to microbiological monitoring and control. Colonization of the ear canal with P. aeruginosa or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Although the same changes have been observed when contact with water was also involved (Wright and Alexander, 1974;Alcock, 1977), our findings, in the absence of any operational diving, confirm that such changes in the aural flora are unavoidably associated with the saturation technique itself. It is this change to a Gram-negative flora in the external auditory meatus that would predispose to the development of otitis externa.…”
Section: Discussionsupporting
confidence: 83%
“…Although the same changes have been observed when contact with water was also involved (Wright and Alexander, 1974;Alcock, 1977), our findings, in the absence of any operational diving, confirm that such changes in the aural flora are unavoidably associated with the saturation technique itself. It is this change to a Gram-negative flora in the external auditory meatus that would predispose to the development of otitis externa.…”
Section: Discussionsupporting
confidence: 83%
“…In 30% of patients suffering from external otitis, P. aeruginosa can be isolated from the external auditory canal [6], Epidemiological studies have shown that P. aeruginosa is highly infectious under favorable circum stances, and its virulence accumulates, with serious epidemics as a result [11]. This may explain the fulminant infections in our otherwise healthy, young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Muth et al [12] in their study observed that SCUBA divers are the most commonly affected by this condition especially in warmer climates. Specifically, saturation divers are a commonly affected category of working divers because they maintain little cerumen due to the constant flushing of the EAC, [10,13,14]. These divers spend days, sometimes weeks, underwater at a great depth, living within a helium-filled confined space to carry out study on a commercial or industrial basis.…”
Section: Otitis Externamentioning
confidence: 99%